DOES THE ABSENCE OF A FATHER FIGURE PLAY A ROLE IN CRIMINALITY? A CORRELATIONAL STUDY OF FATHERLESS AND MORAL DISENGAGEMENT - Suci Mutia; Indriyani Santoso (Causalita, 2025)
This study aims to determine whether fatherless has a relationship with moral disengagement in prisoners in prison X and what form of moral disengagement in prisoners who experience fatherless. This type of research is quantitative research with a correlational approach. Participants in this study were 104 prisoners in prison X. This study uses fatherless as an independent variable and moral disengagement as a dependent variable. Hypothesis testing produces a significance value of 0.043 (p <0.05). The results of this study showed that fatherless has a positive relationship with moral disengagement. In this study, Based on the results of the study, it was concluded that the role of the father felt by the prisoners was in the moderate category, meaning that the role of the father existed but not completely. Then it was also found that prisoners in prison X tended to carry out moral disengagement in the form of distortion of consequences, namely moral justification by distorting others for personal gain and avoiding consequences for actions that harm others. The results of this study indicate that fatherless has a relationship with moral disengagement.